Characteristics of nanostructured CaxZn(1-x)Al2O4 thin films prepared by Sol-Gel method for GPS patch antennas - Wan Nasarudin Wan Jalal,; Huda Abdullah,; Mohd Syafiq Zulfakar,; Sahbudin Shaari,; Mohammad Thariqul Islam,; Badariah Bais, (Universiti Kebangsaan Malaysia, 2014)
CaxZn(1-x)Al2O4 thin films (x = 0.00; 0.05; 0.10; 0.15 and 0.20) were prepared by sol-gel method with the substitution of Zn2+ by Ca2+ in the framework of ZnAl2O4. The effect of Ca addition on the structure and morphology of CaZnAl2O4 thin films was investigated by x-ray diffraction (XRD), field-emission scanning electron microscope (FESEM), energy-dispersive x-ray spectroscopy (EDX), ultra-violet visible (UV-Vis) and atomic force microscope (AFM). The XRD patterns showed the characteristic peaks of face-centred cubic (fcc) ZnAl2O4 and CaZnAl2O4. The addition of Ca increased the crystallite size from 8.9 to 30.2 nm. The bandgap of CaxZn(1-x)Al2O4 thin film was found in the range of 3.40 to 3.84 eV. SEM micrograph shows the morphology of all thin films is sphere-like, with the grain size increased from 33 to 123 nm. The AFM images show the roughness of surface morphology increased. The substitution of Zn2+ by Ca2+ increased the crystallite size, grain size and surface roughness which evidently increased the density (4.59 to 4.64 g/cm3) and dielectric constant (8.48 to 9.54). The composition of CaxZn(1-x)Al2O4 is considered as suitable material for GPS patch antennas.